The Author's Worldview in The Novel of Keluarga Cemara 2 By Arswendo Atmowiloto: A Study of Literary Sociology - Pamungkas, Yoga; Supriyanto, Teguh; Doyin, Muh. (Universitas Negeri Semarang, 2022)
A literary work is inseparable from events, experiences, and also social activities experienced by the authors in real life. In the process, the authors must have a background that underlies why a literary work is created. This study aims to analyze the sociocultural background and the author's worldview reflected in the novel of Keluarga Cemara 2 by Arswendo Atmowiloto. Sociological approach of literature and the genetic structuralism theory were applied in this study. The data were collected by using semiotic reading method. The analysis was carried out through the dialectical method. The results show that 1) the sociocultural background in the novel of Keluarga Cemara 2 consists of the rich and poor community, 2) Arswendo views the poor as people who live with low economic conditions. Financial problem is the main problem mostly faced by the poor. They often get injustice in various ways. In contrast, Arswendo views the rich as people who live with a high economic level. The financial condition of the rich is certainly not a problem. They think that all problems can be solved with money.